Complications after prostate biopsies in men on active surveillance and its effects on receiving further biopsies in the Prostate cancer Research International: Active Surveillance (PRIAS) study. (12th February 2016) - Bokhorst, Leonard P.; Lepistö, Inari; Kakehi, Yoshiyuki; Bangma, Chris H.; Pickles, Tom; Valdagni, Riccardo; Alberts, Arnout R.; Semjonow, Axel; Strölin, Petra; Montesino, Manuel F.; Berge, Viktor; Roobol, Monique J.; et al.
Abstract : Objective: To study the risk of serial prostate biopsies on complications in men on active surveillance (AS) and determine the effect of complications on receiving further biopsies. Patients and methods: In the global Prostate cancer Research International: Active Surveillance (PRIAS) study, men are prospectively followed on AS and repeat prostate biopsies are scheduled at 1, 4, and 7 years after the diagnostic biopsy, or once yearly if prostate‐specific antigen‐doubling time is <10 years. Data on complications after biopsy, including infection, haematuria, haematospermia, and pain, were retrospectively collected for all biopsies taken during follow‐up in men from several large participating centres. Generalised estimating equations were used to test predictors of infection after biopsy. Competing risk analysis was used to compare the rates of men receiving further biopsies between men with and without previous complications. Results: In all, 2 184 biopsies were taken in 1 164 men. Infection was reported after 55 biopsies (2.5%), and one in five men reported any form of complication. At multivariable analysis, the number of previous biopsies was not a significant predictor of infection (odds ratio 1.04, 95% confidence interval 0.76–1.43). The only significant predictor for infection was the type of prophylaxis used. Of all men with a complication at the diagnostic or first repeat biopsy, 21% did not have a repeat biopsy at the time a repeat biopsy was scheduled according to protocol, vs 12% for men without a previous biopsy complication. Conclusion: In our present cohort of men on AS, we found no evidence that repeat prostate biopsy in itself posed a risk of infection. However, complications after biopsy were not uncommon and after a complication men were less likely to have further biopsies. We should aim to safely reduce the amount of repeat biopsies in men on AS.